BIRTH‐ORDER DIFFERENCES CAN DRIVE NATURAL SELECTION ON AGING. (2nd January 2014) - Gillespie, Duncan O. S.; Trotter, Meredith V.; Krishna‐Kumar, Siddharth; Tuljapurkar, Shripad D.
Abstract Senescence—the deterioration of survival and reproductive capacity with increasing age—is generally held to be an evolutionary consequence of the declining strength of natural selection with increasing age. The diversity in rates of aging observed in nature suggests that the rate at which age‐specific selection weakens is determined by species‐specific ecological factors. We propose that, in iteroparous species, relationships between parental age, offspring birth order, and environment may affect selection on senescence. Later‐born siblings have, on average, older parents than do first borns. Offspring born to older parents may experience different environments in terms of family support or inherited resources, factors often mediated by competition from siblings. Thus, age‐specific selection on parents may change if the environment produces birth‐order related gradients in reproductive success. We use an age‐and‐stage structured population model to investigate the impact of sibling environmental inequality on the expected evolution of senescence. We show that accelerated senescence evolves when later‐born siblings are likely to experience an environment detrimental to lifetime reproduction. In general, sibling inequality is likely to be of particular importance for the evolution of senescence in species such as humans, where family interactions and resource inheritance have important roles in determining lifetime reproduction.